Pelatihan Mental Sehat Untuk Pengembangan Resiliensi Guru - Gian Sugiana Sugara; Anandha Putri Rahimsyah; Muhammad Muhajirin (UNIB Press, 2024)
Teachers have a responsibility not only to deliver lesson material, but also to shape the character and mental well-being of students. For this reason, the Guidance and Counseling Study Program at the Muhammadiyah University of Tasikmalaya held a